MANIFESTATIONS OF TEACHER PROFESSIONAL AGENCY IN RELATION TO INTEGRATION OF ICT IN TEACHING - Karaseva, Agnese (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
Drawing on the social domain theory of Derek Layder, this qualitative meta-study study aims to propose a novel typology of school teacher professional agency in relation to the process of information and communication technology (ICT) integration in teaching in Latvian and Estonian schools. The typology is built by understanding teachers’ choices and practices of technology use as both resourced and constrained by various personal, situational, social and contextual factors. The findings are based on semi-structured interviews with Latvian (N=16) and Estonian (N=10) teachers, class observations, and a study on teachers’ information search performance online. Five distinct types of teacher agency manifestation are identified and discussed on three dimensions: pedagogic use of ICT, mediation of students’ uses of ICT, and teachers’ learning about ICT. Implications for in-service teacher training are discussed.